Interval Finite Element Analysis of Truss Systems - Erdolen, Ayse (TURKISH CHAMBER CIVIL ENGINEERS, 2011)
In this work, geometric uncertainties due to fabrication errors and/or thermal changes in truss structures are investigated. The system components' deviations from the nominal dimensions (misfitting) are defined as intervals. Such geometric uncertainties are converted into equivalent nodal loads. In the case of truss systems the Interval Finite Element formulation leads to a linear interval system of equations. The results are illustrated in the problems given as examples.
Keywords: Geometric uncertainty; interval analysis; interval finite elements; fabrication errors; Engineering